Antiangiogenic Agents in Combination With Chemotherapy for the Treatment of Epithelial Ovarian Cancer. Issue 3 (1st March 2012) - Teoh, Deanna; Secord, Angeles Alvarez
Abstract : Objective: The purpose of this review was to provide an overview of angiogenesis, including the rationale for targeting angiogenesis as a treatment strategy for epithelial ovarian cancer (EOC) and to discuss available clinical trial data with antiangiogenic agents in EOC, with a focus on combinations with chemotherapy. Methods: This was a literature review of clinical studies evaluating select antiangiogenic agents in combination with traditional cytotoxic chemotherapy for the treatment of EOC. Results: Several therapies that target angiogenesis-specific pathways are undergoing clinical development for EOC. Although some of these agents have demonstrated single-agent activity for EOC, there is considerable interest in combining this treatment strategy with chemotherapy in an effort to potentially improve treatment benefits in this patient population. Bevacizumab, an anti–vascular endothelial growth factor (VEGF) monoclonal antibody, is the most studied antiangiogenic agent in EOC and has shown efficacy as monotherapy and combined with chemotherapy in both the relapsed/recurrent and first-line settings. However, results from recent phase 3 trials raise questions regarding patient selection and optimal dose, schedule, and duration of bevacizumab therapy. Other agents in various phases of testing include aflibercept (VEGF Trap), a fusion protein that binds all isoforms of VEGF; multitargeted antiangiogenic tyrosine kinase inhibitors (eg, BIBF 1120, cediranib, pazopanib, sorafenib); and AMG 386, a selective angiopoietin inhibitor. Toxicities associated with VEGF inhibition are also a concern with antiangiogenic therapy, including hypertension, proteinuria, thromboses, and gastrointestinal perforation. Conclusions: Results from recently completed and ongoing clinical trials combining antiangiogenic agents with chemotherapy are awaited in hopes of expanding therapeutic options for patients with EOC.